Alcohol induced ultra-fine dispersion of Pt on tuned morphologies of CeO2 for CO oxidation - Meher, Sumanta Kumar (2013)
Controlling the structures of supports and supported phases is important for catalytic applications where synergic effects can play a main role. In this context, we present versatile methods for suitable microstructurization of CeO2 support and improved dispersion of supported Pt crystallites in a Pt/CeO2 system for enhanced catalytic oxidation of CO. The physicochemical properties investigated using SEM, BET, visible Raman, H2-TPR and OSC measurements demonstrated the important role played by the precursor on the properties of CeO2. Further, 0.5 wt% Pt deposited over CeO2 via ethylene glycol assisted reduction (EGR) was found to be more advantageous than conventional impregnation (IMP) in producing very finely dispersed Pt particles that did not noticeably sinter even after thermal treatment at 500 ◦C for longer duration. H2-chemisorption and H2-TPR experiments further substantiated better Pt dispersion on CeO2 prepared in the presence of Cl− ions regardless of the method employed, thus suggesting a strong microstructural effect of support during growth and anti-sintering activity of Pt crystallites. The CO oxidation activity additionally demonstrates that samples prepared by EGR method show remarkably better performance (100% conversion in <100 ◦C) as compared to their impregnated counterparts (100% conversion at ∼300 ◦C). The present approach to improve the catalytic activity of Pt/CeO2 based heteronanocomposites by finely dispersing low concentrations of Pt nanocrystallites over microstructurally tuned CeO2 support is encouraging in the context of designing novel metal–metal oxide based catalysts for astute potential applicability under vibrantly testing conditions.